Acceptance of generic medicines by patients (Research, Society and Development, 2023)
The objective of the present study was to identify factors related to patients' acceptance of generic medications through field research. To achieve the proposed objective, an exploratory/descriptive qualitative research was developed. A questionnaire was administered to 116 volunteers, predominantly women (71%) and young adults (82% between 18 and 30 years old). The preference for large pharmacies (chains and franchises) and the varied patterns of medication use stand out, with 51% reporting infrequent use and 29% reporting daily use. There is a significant acceptance of generic medicines (97.5%), driven mainly by the price factor (69%). Confidence in the equivalence of effect between generic and reference medicines is high (71.5%). The research suggests a change in consumer perception regarding large pharmaceutical chains. The emphasis on price in purchasing decisions indicates significant implications for healthcare professionals and the pharmaceutical industry, with potential direction to improve access and patient experience. The diversity in medication use patterns highlights the need to understand the motivations underlying these behaviors. These results provide valuable information for future public health initiatives and policies.